SP0157 Delivering Technology Enabled Care Services in Primary Care. (15th July 2016) - Chambers, R.
Abstract : Background: there are many pilots of various types of technology enabled care in general practice settings in the UK. The challenge is to integrate such technology as a natural option for delivery of care in specific pathways or for particular patient groups, across and between healthcare settings. Project: Adoption of technology enabled care in Staffordshire and beyond in general practice settings, and interacting with clinicians in acute care, mental health and community settings, and pharmacies. Modes of technology included locally evolved apps, Flo telehealth, skype and videoconsultations with encrypted mode, social media (eg Facebook); foci included patients with asthma, COPD, heart failure, hypertension, AF and other conditions. The presentation will capture challenges and how these have been overcome. Discussion: How do we in the NHS match patients' needs and preferences for technology enabled care? How do we prove to the commissioners of care and frontline practitioners that technology enabled care is worth doing? Disclosure of Interest: None declared